The effect of mountain pine beetle caused mortality on subalpine forest stand and landscape structure in Rocky Mountain National Park, CO - Nelson, Kellen N., author; Rocca, Monique Elisabeth, 1974-, advisor; Binkley, Dan, committee member; Martin, Patrick, committee member (Colorado State University. Libraries, 2009)
Mountain pine beetle (MPB) eruptions in lodgepole pine forests are a disturbance process that shape forest structure and successional trajectories. Chapter one examines the effect that MPB have on overstory stand and landscape forest structure. I distributed 46 randomly located clusters of three plots across the west side of Rocky Mountain National Park (RMNP), and characterized changes in stand structure and lodgepole pine mortality through three stages in the eruption. Across the landscape, diameter at breast height, basal area, and density decreased by 37%, 71%, and 34% respectively. Environmental factors (elevation and moisture) and tree size greatly influenced the early stage of the eruption; whereas later stages showed stronger relationships with stand structure factors (tree size, basal area, proportion of non-host trees, density and stand age). Changes in forest heterogeneity depended on spatial scales; at the local scale, heterogeneity increased among subplots within clusters, while heterogeneity among clusters declined over time. In chapter two, I explored the effect of MPB-related mortality on aspen regeneration by examining whether suckering densities and growth rates increase with MPB-related mortality, and if ungulates utilize additional suckers through browsing. Conifer overstory mortality, aspen sucker density, stem elongation, total sucker height, and ungulate browsing rates were characterized in 48 plots over 8 stands. Heavy lodgepole pine mortality decreased conifer basal area by 80% and stem density by 50% of pre-eruption levels. This appears to relieve competitive pressure on aspen in mixed conifer-aspen stands. Linear mixed-effects model results show that as weighted mortality increased, aspen sucker density increased three-fold, aspen stem elongation increases by 2.5-fold, and mean sucker height increases by two-thirds. Additionally, as sucker density increased, I did not find evidence to suggest that the rate of ungulate browsing increased. Mountain pine beetle related mortality relieves conifer pressure and may lead to successful aspen recruitment.
Department Head: Michael J. Manfredo.